Unraveling the associations and causalities between glucose metabolism and multiple sleep traits - Yi, Minhan; Fei, Quanming; Chen, Ziliang; Zhao, Wangcheng; Liu, Kun; Jian, Shijie; Liu, Bin; He, Meng; Su, Xiaoli; Zhang, Yuan (Frontiers in Endocrinology, 2023)
Purpose: The aim of our study is to estimate the associations and causalities of glucose metabolism traits of fasting blood glucose (FBG), fasting insulin (FINS), glycosylated hemoglobin (HbA1c), and 2 hour-glucose post-challenge (2hGlu) with sleep traits, containing excessive daytime sleepiness (EDS), insomnia and sleep duration. Methods: We employed standard quantitative analysis procedures to assess the associations between sleep traits and glucose metabolism. Besides, we acquired published genome-wide association studies (GWAS) summary statistics for these traits and conducted Mendelian Randomization (MR) analyses to estimate their causal directions and effects. The inverse variance weighting (IVW) was employed as the primary approach, followed by sensitivity analyses. Results: A total of 116 studies with over 840,000 participants were included in the quantitative analysis. Our results revealed that participants with abnormal glucose metabolism had higher risks for EDS (OR[95%CI]=1.37[1.10,1.69]), insomnia (OR[95%CI]=1.65[1.24,2.20]), and both short and long sleep duration (OR[95%CI]=1.35[1.12,1.63]; OR[95%CI]=1.38[1.13,1.67] respectively). Also, individuals with these sleep traits exhibited alterations in several glycemic traits compared with non-affected controls. In MR analysis, the primary analysis demonstrated causal effects of 2hGlu on risks of EDS (OR[95%CI]=1.022[1.002,1.042]) and insomnia (OR[95%CI]=1.020[1.001,1.039]). Also, FINS was associated with short sleep duration (OR[95%CI]=1.043[1.018,1.068]), which reversely presented causal influence on HbA1c (β[95%CI]=0.131[0.022,0.239]). These results were confirmed by sensitivity analysis. Conclusion: Our results suggested mutually risk and causal associations between the sleep traits and glycemic traits, shedding new light on clinical strategies for preventing sleep disorders and regulating glucose metabolism. Future studies targeting these associations may hold a promising prospect for public health.